(untitled) (Raparin Journal of Humanities (RJH), 2024)
In this study, we tried to shade light on effect of precipitation on the underground water level in Central Sulaimani Province, based on collected data of precipitation of different weather station in Sulaimani, Bakrajo, Bazyan. Data of all the wells, in practical fields using electrical sounder for measuring weather levels. GPS was also used to detect the astronomical position of the wells and define their places on map using ArcGis10.8. On two different time periods, the water levels were measured including Autumn, when the underground water position is in its mining level, from 17-9-2021 to 13-11-2021, and on Spring from 4-3-2022 to 17-4-2022 when water is at lightest level. To compare water levels before and after precipitation, another method of quantitative analysis based on statistical results and Pearson Coefficient to realize correction of degree of precipitation and underground water levels. Moreover, effect of precipitation on underground water level has been shown using SPSS-26. The aim of this research is to define the relation and precipitation effects on underground water level, and ultimately propose a scientific plan to preserve the underground water level. As a result, according to Pearson Coefficient Correlation, there is negative relation between precipitation and the depth of underground water level. This means that the depth to reach underground water is reduced when the precipitation increases. Furthermore; precipitation has an estimated effect of 90.2% on static level of underground water, and of 67.6% on dynamic level of underground water.